Uma análise dos incidentes com tubarões na zona metropolitana do Recife - Pernambuco - Santos, Erik Antonio Ferreira dos (2022)
The construction of the Governador Eraldo Gueiros Industrial Port Complex, popularly known as Porto de Suape, in the 1980s, is considered by specialists to be the primary factor resulting from the incidents with sharks in the city of Recife (Pernambuco) and its metropolitan area. This work sought to explain the reasons that led to the associa- tion of these incidents with the construction of the port, discussing the environmental impacts caused by the construction of the port complex, the study also raises statistical data on the incidents and discusses characteristics and behaviors of the species iden- tified in the raids. An educational product was also developed, a profile on the social network Instagram, which has curiosities about the phenomenon and reinforces socio- educational prevention measures.